2021
DOI: 10.3390/ijerph18168678
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Ethanol-Induced Cerebellar Ataxia: Underpinnings of Neuronal Death in the Cerebellum

Abstract: Ethanol consumption remains a major concern at a world scale in terms of transient or irreversible neurological consequences, with motor, cognitive, or social consequences. Cerebellum is particularly vulnerable to ethanol, both during development and at the adult stage. In adults, chronic alcoholism elicits, in particular, cerebellar vermis atrophy, the anterior lobe of the cerebellum being highly vulnerable. Alcohol-dependent patients develop gait ataxia and lower limb postural tremor. Prenatal exposure to et… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 95 publications
2
20
0
Order By: Relevance
“…The incidence of other postoperative complications is high, which is not conducive to the recovery of patients. Even when patients' lives can be saved, these complications may lead to lifelong disability [ 23 ]. With the development of medical technology, microsurgery has been applied to various cardiovascular and cerebrovascular diseases.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of other postoperative complications is high, which is not conducive to the recovery of patients. Even when patients' lives can be saved, these complications may lead to lifelong disability [ 23 ]. With the development of medical technology, microsurgery has been applied to various cardiovascular and cerebrovascular diseases.…”
Section: Discussionmentioning
confidence: 99%
“…It has been proposed that alcohol-induced cerebellar degeneration requires a large amount of daily alcohol drinking (>140 g or 50 ounces of wine per day, approximately 10 times of a standard drink) for more than 10 years. 23 24 A study found that this amount of alcohol is associated with cerebellar vermis atrophy identified by a computed tomography imaging study in 41 cases attributed to alcohol use. 23 On the other hand, a small amount of daily alcohol ingestion with 5 g for a similar length of time can also lead to ataxia.…”
Section: Alcohol-induced Cerebellar Ataxiamentioning
confidence: 99%
“…Bowel, bladder, and sexual dysfunction may occur with peripheral nerve involvement 7-9. The central nervous system effects include a deficit in cognitive ability, severe impairment in memory, and degradation of the cerebellum, causing cerebellar ataxia–difficulty with muscle movement, coordination, postural stability, and balance–from a deficiency in B vitamins, particularly thiamine 6-9,17,18,24…”
Section: Effects On Body Organs and Systemsmentioning
confidence: 99%